تنمية بعض مهارات إدارة الفصل اللازمة لمعلمي المرحلة الأولي من التعليم الأساسي على ضوء المعايير القومية للمعلم - علي، حسين علي أحمد (جامعة المنيا - كلية التربية, 2023)
هدفت الدراسة إلى: تنمية بعض المهارات اللازمة لمعلمي المرحلة الأولى من التعليم الأساسي؛ لتنمية مهارات إدارة الفصل لديهم على ضوء المعايير القومية لمعلم هذه المرحلة. وتحددت مشكلة الدراسة في الإجابة عن السؤال الرئيس التالي: " كيف يمكن تنمية مهارات إدارة الفصل لدى معلمي المرحلة الأولى من التعليم الأساسي على ضوء المعايير القومية للمعلم في محافظة المنيا؟"، وفي سبيل تحقيق أهداف الدراسة تم استخدام المنهج الوصفي، وتم تصميم الاستبانة باستخدام مقياس ليكرت الثلاثي؛ لتقيس: (درجة الممارسة ودرجة الأهمية) لهذه المهارات، وتضمنت (54) عبارة، وتم تقسيمها إلى قسمين الأول: يتناول بعض البيانات الأساسية للمدرسة وبعض المتغيرات الديموغرافية للمفحوصين، والثاني: يتناول المحاور الثلاثة للاستبانة كالآتي: المحور الأول (بعض المهارات الشخصية) بعدد (15) عبارة، والمحور الثاني (بعض المهارات الإدارية) بعدد (17) عبارة، والمحور الثالث (بعض المهارات المهنية) بعدد (22) عبارة، وضم كل محور منهم ثمان مهارات. وتكونت عينة الدراسة من (361) معلما من معلمي المرحلة الأولى من التعليم الأساسي ببعض مدارس هذه المرحلة في الإدارات التعليمية التسعة بمحافظة المنيا. وتوصلت الدراسة النظرية إلى عدة نتائج منها أن: التنمية الفعالة لمعلم هذه المرحلة تبدأ من داخله أولا، وأن الحضور والمشاركة الإيجابية في الدورات التدريبية المعتمدة والمنظمة التي يحتاج إليها معلم هذه المرحلة، ينقل العديد من الخبرات والمعارف والقيم الهامة له. وتوصلت الدراسة الميدانية إلى: أنه لا توجد فروق ذات دلالة إحصائية بين متغير المؤهل الدراسي ودرجتي الممارسة والأهمية؛ وذلك لتقارب نسب المتوسطات بينهما، وكذلك لا توجد فروق ذات دلالة إحصائية بين متغير المسمى الوظيفي ودرجتي الممارسة والأهمية؛ وذلك لتقارب نسب المتوسطات بينهما أيضا. وإلى أن نسبة متوسط الاستجابة في بعد (درجة الأهمية) أعلى من نسبة متوسط الاستجابة في بعد (درجة الممارسة) للاستبانة ككل. وقد أوصت الدراسة بـ؛ ضرورة تنفيذ الحلول المقترحة بالتعاون والتنسيق بين وحدات التدريب داخل المديريات التعليمية وتحت إشرافها، والإدارات والمدارس التابعة لها، وإقامة تدريبات وندوات علمية متخصصة لمعلمي هذه المرحلة من قبل التوجيه المختص لكل مادة دراسية، وإجراء زيارات ميدانية بين المعلمين؛ لتبادل الخبرات فيما بينهم. The study aimed at developing some of the necessary skills for teachers of the first stage of basic education; To develop their classroom management skills in light of the national standards for the teacher of this stage. The problem of the study was determined in answering the following main question: “How can the classroom management skills of teachers of the first stage of basic education be developed in the light of the national standards for teachers in Minia Governorate?”, In order to achieve the objectives of the study, the descriptive approach was used, and the questionnaire was designed using a scale triple likert; To measure: (the degree of practice and the degree of importance) of these skills, it included (54) phrases, and it was divided into two parts. The first: deals with some basic data for the school and some demographic variables for the subjects, and the second: deals with the three axes of the questionnaire as follows: The first axis (some personal skills) with a number of (15) a phrase, and the second axis (some administrative skills) with (17) phrases, and the third axis (some professional skills) with (22) phrases, and each axis included eight skills. The study sample consisted of (361) teachers of the first stage of basic education in some schools of this stage in the nine educational departments in Minia Governorate. The theoretical study reached several results, including that: the effective development of the teacher of this stage starts from within him first, and that attendance and positive participation in the approved and organized training courses that the teacher of this stage needs; He conveys many important experiences, knowledge and values to him. The field study concluded: that there are no statistically significant differences between the academic qualification variable and the degree of practice and importance; This is due to the convergence of the ratios of the averages between them, as well as there are no statistically significant differences between the job title variable and the degree of practice and importance; This is due to the convergence of the ratios of the averages between them as well. And that the ratio of the average response in the dimension (degree of importance) is higher than the ratio of the average response in the dimension (degree of practice) for the questionnaire as a whole. The study recommended: The necessity of implementing the proposed solutions in cooperation and coordination between the training units within the educational directorates and under their supervision, and the departments and schools affiliated to them, and the establishment of specialized scientific training and seminars for teachers of this stage by the competent guidance of each subject, and conducting field visits among teachers; To exchange experiences with each other.
Keywords: مدارس التعليم الأساسي -- المشكلات الصفية -- الممارسات المهنية -- أعداد المعلم -- مصر